2007
DOI: 10.4315/0362-028x-70.5.1277
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Processed Vegetable Salads: Microbial Quality Evaluation

Abstract: The increasing demand for fresh fruits and vegetables and for convenience foods is causing an expansion of the market share for minimally processed vegetables. Among the more common pathogenic microorganisms that can be transmitted to humans by these products are Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella. The aim of this study was to evaluate the microbial quality of a selection of minimally processed vegetables. A total of 181 samples of minimally processed leafy salads were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
3
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 21 publications
11
63
3
9
Order By: Relevance
“…As for the MPN of coliforms at 45º, the results are similar to those obtained by BRANDÃO et al (2014) in Brazil, showing a 20% prevalence of values above the standard limits in salad samples from restaurants, although lower than the results obtained in other studies conducted in Brazil, which showed a prevalence of 70% in samples of minimally processed salads originating from supermarkets (FRÖDER et al, 2007) and 100% in salads originating from restaurants (ROCHA et al, 2014) with values above 100 MPN/g.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As for the MPN of coliforms at 45º, the results are similar to those obtained by BRANDÃO et al (2014) in Brazil, showing a 20% prevalence of values above the standard limits in salad samples from restaurants, although lower than the results obtained in other studies conducted in Brazil, which showed a prevalence of 70% in samples of minimally processed salads originating from supermarkets (FRÖDER et al, 2007) and 100% in salads originating from restaurants (ROCHA et al, 2014) with values above 100 MPN/g.…”
Section: Discussionsupporting
confidence: 84%
“…in raw salads of restaurants in Pombal, in Paraiba state. In other studies carried out in UAN by FRÖDER et al (2007), DIAS et al (2011) andMAISTRO et al (2012), the prevalence of Salmonella spp. in salad samples was 3, 28.57 and 16.86%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A low occurrence of this pathogen in minimally processed vegetables has been reported by other authors [15,16,17].…”
Section: Resultsmentioning
confidence: 56%
“…Studies in the fruit and vegetable sector have demonstrated the importance of the hygienic design of equipment and the sanitation of equipment (e.g., Lehto et al, 2011;Rapanello, Fuzihara, Nunes, Daros, & Savignano, 2009;, and the personal, and especially hand hygiene of workers in the field and in companies (e.g., Fonseca, 2006;Michaels & Todd, 2005;. Moreover, the maintenance of sprayers, packaging and other equipment (e.g., Abhilash & Singh, 2009;Garrett, 2009), and the incoming control of materials (such as, planting materials, fertilizers, pesticides at primary production), produce and ingredients in the next chain stages (e.g., Froder et al, 2007;Leifert, Ball, Volakakis, & Cooper, 2008) have been stated as important measures for preventing microbial and chemical contamination of fresh produce. Therefore, the indicators to assess these activities from the main principles for FSMS assessment have been included in our tool (Luning et al, 2008).…”
Section: Preventive Control Activitiesmentioning
confidence: 99%